VIGOR BENIH KACANG HIJAU PADA BUDIDAYA TANPA OLAH TANAH DENGAN APLIKASI PUPUK FOSFAT DOSIS RENDAH YANG DITANAM SETELAH PADI SAWAH - Ichwan Madauna (Universitas Tadulako, 2007)
Field trial was conducted in the farming area in Parigi Moutong regency. Vigor test was performed in the SeedTechnology Laboratory, Agronomy Department Faculty of Agriculture Tadulako University. This trial lasted from 5 Februaryto 16 July 2006. The aim of this trial was to evaluate the effect of non-tillage and the application of low dosage Phosphorusfertilizer in the rice-field following rice sowing on the initial vigor of mung bean seeds produced. This trial used BlockRandomized Design in factorial pattern with three replications. Two factors tested, namely non-tillage practices with fourlevels, namely non-tillage, non-tillage + mulching, non-tillage + glyphosate, and non-tillage + mulching + glyphosate. Thesecond factor was Phosphorus fertilizer with four levels, namely without Phosphorus fertilizer, 1/3 of recommendedPhosporous fertilizer dosage (30 kg P2O5/ha); 2/3 of recommended Phosphorus fertilizer dosage (60 kg P2O5/ha); and as ofrecommended Phosphorus fertilizer dosage (90 kg P2O5/ha). Differences between treatment were determined by using LeastSignificant Difference test at 5% and 1%. Results of this tial showed that Phosporous fertilizer and non-tillage system did nothave interaction. Application of Phosphorus ar recommended dosage had the highest dried-seed yield per hectare, germination(97,50 %) and germination rate (29,457 %)Keywords : Seed vigor, non-tillage, and Phosphorus